Hâ Control of Polynomial Fuzzy Systems: A Sum of Squares Approach - Bomo S. Wibowo; Bambang Riyanto Trilaksono; Arief Syaichu-Rohman (Journal of Engineering and Technological Sciences, 2014)
This paper proposes the control design ofa nonlinear polynomial fuzzy system with Hâ performance objective using a sum of squares (SOS) approach. Fuzzy model and controller are represented by a polynomial fuzzy model and controller. The design condition is obtained by using polynomial Lyapunov functions that not only guarantee stability but also satisfy the Hâ performance objective. The design condition is represented in terms of an SOS that can be numerically solved via the SOSTOOLS. A simulation study is presented to show the effectiveness of the SOS-based Hâ control designfor nonlinear polynomial fuzzy systems.